2020
DOI: 10.3389/fgene.2020.566579
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Analysis Discovers Microtubular Tubulin Beta 6 Class V (TUBB6) as a Potential Therapeutic Target in Glioblastoma

Abstract: Glioblastoma (GBM) has long been a major clinical research challenge to scientists. The pivotal role of the mitochondria related gene family in the promotion of GBM tumorigenesis is not clear. We detected that microtubular tubulin beta 6 class V (TUBB6) was one of 33 differentially expressed mitochondrial-focused genes (DEMFGs) in GBM, and considered that TUBB6 is a potential therapeutic target in GBM. TUBB6 was vital for GBM and marked as the key prognostic gene in primary GBM. Mutations of TUBB6 in GBM were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 44 publications
2
16
0
Order By: Relevance
“…As expected, we observed higher expression of cell cycle genes and lower expression of p53 tumor suppressor gene expression in hGSCs than that in hNSCs. We have analyzed the 10 GBM-related genes reported recently (Jiang et al, 2020;Larsson et al, 2020;Yang et al, 2020) and six of them showed expression differences between hGSCs and hNSCs, further validating our hGSC derivation approach.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…As expected, we observed higher expression of cell cycle genes and lower expression of p53 tumor suppressor gene expression in hGSCs than that in hNSCs. We have analyzed the 10 GBM-related genes reported recently (Jiang et al, 2020;Larsson et al, 2020;Yang et al, 2020) and six of them showed expression differences between hGSCs and hNSCs, further validating our hGSC derivation approach.…”
Section: Discussionsupporting
confidence: 73%
“…In contrast, the expression of the p53 tumor suppressor gene was lower in hGSCs than that in hNSCs ( Figure 5E ). IGFB2 and tubulin beta 6 class V (TUBB6), two potential therapeutic targets in GBM treatment ( Jiang et al, 2020 ), both displayed significantly lower expression in hGSCs than in hNSCs ( Figure 5F ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TUBB6 is a member of the beta tubulin superfamily, which is a major component of microtubules, and has a molecular weight of approximately 50 kDa [31]. TUBB6 contributes to many cellular processes, such as structural support, intracellular transport, and DNA segregation [32]. Nrf2 is a nuclear transcription factor, which plays an important role in TBI [33].…”
Section: Discussionmentioning
confidence: 99%
“…We have been working on basic research on gliomas and anti-tumor medicinal plants, including gene clusters, tumor markers [8], and noncoding RNA-based translational medicine research [9]. For example, we identified the potential role of SRY-Box Transcription Factor 6 (SOX6) in GBM [10]; and analyzed the gene set of mitochondrial metabolism-related genes and discovered the importance of Annexin A2 (ANXA2), S100 Calcium Binding Protein A11 (S100A11), and Tubulin Beta 6 Class V (TUBB6) as prognostic factors for GBM [11]. We found the function of sugar transporters (SWEETs) in camellia flower development in the early tea tree [12], while the sugar transporter homologous to humans and plants is Solute Carrier Family 50 Member 1 (SLC50A1).…”
Section: Introductionmentioning
confidence: 99%